An Equity Lens on Science Education Reform-Driven Classroom-Embedded Assessments. (1st October 2020) - Mark, Sheron L.; Tretter, Tom; Eckels, Lacey; Strite, Amy
ABSTRACT: Long-standing calls have been initiated to attend to equity in student achievement in and through science. Science teacher educators can aid these efforts by identifying effective science teaching strategies and supporting K–12 science teachers in integrating those into their practice. Scholars argue for an equity-driven lens to be central in teacher education for reform efforts to be fully effective in ensuring high quality education for all students. The Next Generation Science Standards (NGSS) undergird current U.S. reform efforts and are noted for more explicitly addressing issues of equity than past standards, but still noted as limited as equity is not sufficiently central. Additionally, reflexivity is encouraged with reforms, where thorough understanding is derived of effectiveness and challenges of past and current practices before implementing changes. Altogether, these issues inform the current study: an exploration of the ways in which science teachers work to implement NGSS-aligned instruction within a professional development context where an equity-driven lens is not explicit, seeking to identify evidence of how current practice facilitated or aligned with equity-driven practices. This inquiry will serve to guide future efforts to build on and transform current practice to more centrally address equity in science education.